2005
DOI: 10.1093/jat/29.7.734
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Absorption and Distribution of Methanol in a Homicide

Abstract: A woman was alleged to have committed suicide by consuming a gasoline additive shortly before jumping from a second floor balcony within her home. She was found dead by police with a multitude of injuries, lying nude in a partially evaporated unknown residue that was later determined to be methanol. Samples collected at autopsy were found to contain methanol in the following concentrations: femoral blood 31.2 mg/dL, pulmonary artery blood 111.0 mg/dL, aortic blood 77.8 mg/dL, vitreous fluid 196.4 mg/dL, brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Methyl alcohol poisoning has been mainly reported in community as accidents or crimes by oral ingestion [4] or transdermal absorption [5, 6]. Two industrial cases of methyl alcohol intoxication were found in a poorly ventilated laboratory chronically [7] and a methyl alcohol production factory with acute exposure [8].…”
Section: Discussionmentioning
confidence: 99%
“…Methyl alcohol poisoning has been mainly reported in community as accidents or crimes by oral ingestion [4] or transdermal absorption [5, 6]. Two industrial cases of methyl alcohol intoxication were found in a poorly ventilated laboratory chronically [7] and a methyl alcohol production factory with acute exposure [8].…”
Section: Discussionmentioning
confidence: 99%
“…As regards to these difficulties most of the reported cases include post mortem findings. [4][5][6][7][8] This report has a target on highlighting the importance of diagnosis and management of methanol poisoning in a case that methanol was transdermally ingested and the patient was completely ignorant of its use. Our patient used a high methanol solvent-containing dressing to cure selulitis in her leg and skin penetration seriously affected her.…”
Section: Discussionmentioning
confidence: 99%
“…3 The lethal dose has been reported to be 1 ml.kg -1 with permanent visual disturbances occurring after exposure to as little as 0.1 ml.kg -1 . 4 We present a case that transdermal methanol intoxication was treated in a lately admitted patient who was unintentionally exposed to methanol.…”
Section: Accidental Transdermal Methanol Poisoningmentioning
confidence: 99%
“…Methanol poisoning causes neurological sequelae of variable severity including cerebral and intraventricular hemorrhage, cerebellar necrosis, diffuse cerebral edema, bilateral subcortical white matter necrosis, and optic neuropathy 1–4. Ingestion of even small amount of methanol can cause vision loss in a few hours 2.…”
Section: Introductionmentioning
confidence: 99%